2018
DOI: 10.3389/fmicb.2018.03042
|View full text |Cite
|
Sign up to set email alerts
|

Engineered Streptomyces lividans Strains for Optimal Identification and Expression of Cryptic Biosynthetic Gene Clusters

Abstract: Streptomyces lividans is a suitable host for the heterologous expression of biosynthetic gene clusters (BGCs) from actinomycetes to discover “cryptic” secondary metabolites. To improve the heterologous expression of BGCs, herein we optimized S. lividans strain SBT5 via the stepwise integration of three global regulatory genes and two codon-optimized multi-drug efflux pump genes and deletion of a negative regulatory gene, yielding four engineered strains. All optimization steps were observed to promote the hete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 59 publications
0
36
0
Order By: Relevance
“…We have previously demonstrated that pJTU6728, an attP ϕ BT 1 -based integrative plasmid carrying the transcription factor gene nusG , the global regulator gene afsS cla , and the two drug-efflux pump genes mdfA co and lrmA co , increased the heterologous production of secondary metabolites in an S. lividans host ( Peng et al, 2018 ). To assess the effects of pJTU6728 on the heterologous production of actinorhodin in Sac.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously demonstrated that pJTU6728, an attP ϕ BT 1 -based integrative plasmid carrying the transcription factor gene nusG , the global regulator gene afsS cla , and the two drug-efflux pump genes mdfA co and lrmA co , increased the heterologous production of secondary metabolites in an S. lividans host ( Peng et al, 2018 ). To assess the effects of pJTU6728 on the heterologous production of actinorhodin in Sac.…”
Section: Resultsmentioning
confidence: 99%
“…spinosa NRRL18395. pJTU6728 is a derivative of the integrative vector pMS82 and carries the integration site attP and int loci of the Streptomyces temperate phage ϕBT1 ( Gregory et al, 2003 ) and contains the transcription factor gene nusG , global regulator genes afsRS cla , and the two drug efflux pump genes mdfA co and lrmA co ( Peng et al, 2018 ). pJTU6728 was used to improve the production of heterologous antibiotics in Sac.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mathematical estimations point out that Streptomycetes are able to produce around 100,000 antibiotics and only 3% of them have been discovered [ 15 ]. Similarly, the existence of cryptic biosynthetic gene clusters (BGCs) suggests a higher capacity of antibiotic production in those organisms [ 16 , 17 , 18 ].…”
Section: Overview Of Ca Biosynthesis In S Clavuligerus mentioning
confidence: 99%
“…Atratumycin (Yang et al, 2019) Neoabyssomicin/abyssomicin (Tu et al, 2018) Avermectins (Deng et al, 2017) Murayaquinone (Peng et al, 2018) FAC libraries…”
Section: Dna Fragmentationmentioning
confidence: 99%